2017
DOI: 10.2527/tas2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lactation feed intakes for sows with extended lactation lengths

Abstract: The objectives of this research were to quantify and model daily feed intakes to 28 d of lactation in modern sows. A total of 4,512 daily feed intake (DFI) records were collected for 156 Hypor sows from February 2015 to March 2016. The mean lactation length was 27.9 ± 2.0 d. The data included 9 parity 1, 33 parity 2 and 114 parity 3+ sows. Data were collected using a computerized feeding system (Gestal Solo, JYGA Technologies, Quebec, Canada). The feeding system was used to set an upper limit to DFI for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
(37 reference statements)
1
3
1
Order By: Relevance
“…As a result, they found two clusters or feeding curves and concluded that both curves were similar after 5 d of lactation. A possible reason for the difference between the previous two studies [ 13 , 19 ] and our results might be that they did not categorize the feeding curves into some patterns by a decrease for individual DFIs of sows. Our results are similar to a previous U.S.A. study which categorized individual DFIs into six patterns using a major drop, a minor drop, a rapid increase, a gradual increase, low DFI only in early lactation and low DFI throughout lactation [ 11 ].…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…As a result, they found two clusters or feeding curves and concluded that both curves were similar after 5 d of lactation. A possible reason for the difference between the previous two studies [ 13 , 19 ] and our results might be that they did not categorize the feeding curves into some patterns by a decrease for individual DFIs of sows. Our results are similar to a previous U.S.A. study which categorized individual DFIs into six patterns using a major drop, a minor drop, a rapid increase, a gradual increase, low DFI only in early lactation and low DFI throughout lactation [ 11 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Concerning the differences reported by Cabezón et al [ 13 ] from day 18 onwards, it is worth noting that in the current study, once the peak of lactation is reached (around day 18), it is observed that the patterns show small variations in the slope (see normalized feed intake graph; Fig. 1 ).…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations